THE EFFECT OF CURCUMIN ON THE PROLIFERATION AND EXTRACELLULAR MATRIX PRODUCTION IN ETHANOL-INDUCED HEPATIC STELLATE CELLS - RAHMANIAH, RAHMANIAH; LOUISA, MELVA; WARDHANI, BANTARI W. K.; SOETIKNO, VIVIAN (International Journal of Applied Pharmaceutics, 2019)
Objectives: In various liver disease models, including those for alcoholic liver diseases, curcumin, a polyphenolic compound derived from Curcuma longa, is known to have an hepatoprotective effect. However, the mechanism of action underlying its effects on alcohol-induced hepatic fibrosis remains unknown. We aimed to investigate the mechanisms of action underlying the effects of curcumin, mainly involving the transforming growth factor (TGF)-β/Smad pathway. Methods: Hepatic stellate cells (HSCs), LX2, were incubated with 50 mM ethanol with or without curcumin (1 and 10 μM). Viable HSCs were counted using a LUNATM automated cell counter, whereas the expressions of TGF-β, Smad3, tissue inhibitor of metalloproteinases-1 (TIMP-1), and type 1 collagen mRNA were measured using quantitative reverse transcriptase polymerase chain reactions. Results: Curcumin significantly suppressed ethanol-induced HSCs proliferation. The antiproliferative effect of curcumin appeared to be dose dependent. In addition, the mRNA expressions of TGF-β, Smad3, TIMP-1, and type 1 collagen decreased in the cells treated with curcumin. Conclusion: Curcumin seems to attenuate ethanol-induced HSCs proliferation through the suppression of TGF-β and appears to reduce the production of extracellular matrix as shown by the decreased expression of type 1 collagen.